Human capital for the green economy - Kozera-Kowalska, Magdalena (Economics and Environment, 2024)
This study aims to assess the market availability of human capital for the needs of the green economy under the conditions of the changing labour market in Poland. It is a theoretical and analytical study based on desk research and critical analysis of available factual information. Based on an analysis of quantitative data describing the age structure and education of Poles from the perspective of three consecutive decades, a growing labour supply deficit was found. It also points to a possible shortage of competencies needed to green the economy. It was emphasised that, in view of the low effectiveness of the state's prevention policy aimed at preventing the growing demographic crisis, it would be necessary to supplement the shortage of workers from external resources, that is, labour migration. However, this may also be difficult because the labour markets in other European countries become increasingly competitive. Recommended solutions to foster labour market sustainability for the green economy may be to delay the exit of employees from the labour market, boost female economic activity, and make the education system more efficient.